2015
DOI: 10.1107/s205698901501779x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of strontium dinickel iron orthophosphate

Abstract: The transition metal orthophosphates SrM 2Fe(PO4)3 (M = Co, Ni) crystallize in an α-CrPO4-type structure. The chains characterizing this structure are then built up from [Ni2O10] units alternating with [PO4] tetra­hedra and [FeO6] octa­hedra. The structure is nearly the same as that observed in MMnII 2MnIII(PO4)3 (M = Pb, Sr, Ba).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Those studies involved the synthesis and structural characterization of new phosphates such as Na 2 Co 2 Fe(PO 4 ) 3 (Bouraima et al, 2015) and Na 1.67 Zn 1.67 Fe 1.33 (PO 4 ) 3 (Khmiyas et al, 2015) belonging to the alluaudite-type structure group. In addition, divalent and trivalent transition-metal-based phosphates, such as SrNi 2 Fe(PO 4 ) 3 (Ouaatta et al, 2015) and MMn II 2 Mn III (PO 4 ) 3 (M = Pb, Sr, Ba) (Alhakmi et al, 2013a,b;Assani et al, 2013) have been shown to adopt the -CrPO 4 structure type.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Those studies involved the synthesis and structural characterization of new phosphates such as Na 2 Co 2 Fe(PO 4 ) 3 (Bouraima et al, 2015) and Na 1.67 Zn 1.67 Fe 1.33 (PO 4 ) 3 (Khmiyas et al, 2015) belonging to the alluaudite-type structure group. In addition, divalent and trivalent transition-metal-based phosphates, such as SrNi 2 Fe(PO 4 ) 3 (Ouaatta et al, 2015) and MMn II 2 Mn III (PO 4 ) 3 (M = Pb, Sr, Ba) (Alhakmi et al, 2013a,b;Assani et al, 2013) have been shown to adopt the -CrPO 4 structure type.…”
Section: Chemical Contextmentioning
confidence: 99%
“…In this context, new phosphates adopting the alluaudite or -CrPO 4 structure type have been synthesized and structurally characterized. For example, the mixed-valence manganese phosphates PbMn II 2 Mn III (PO 4 ) 3 (Alhakmi et al, 2013) and PbMn II 2 Mn III (PO 4 ) 3 (Assani et al, 2013), the magnesium phosphate NaMg 3 (PO 4 )(HPO 4 ) 2 (Ould Saleck et al, 2015) and silver nickel phosphate Ag 2 Ni 3 (HPO 4 )-(PO 4 ) 2 (Assani et al, 2011) were synthesized by hydrothermal methods, while solid-state reactions were applied to synthesize SrNi 2 Fe(PO 4 ) 3 (Ouaatta et al, 2015) and Na 2 Co 2 Fe(PO 4 ) 3 (Bouraima et al, 2015). In a continuation of the latter preparation route, we have investigated pseudo-quaternary systems MO-NiO-Fe 2 O 3 -P 2 O 5 (M represents a divalent cation) and report here on the synthesis and crystal structure of the title compound, CaNi 2 Fe(PO 4 ) 3 .…”
Section: Chemical Contextmentioning
confidence: 99%
“…Notes: DNP = diffraction des neutrons sur poudre; DRXM = diffraction des rayons X sur moncristal; DRXP = diffraction des rayons X sur poudre; & = site vacant. Ré férences: (a) Glaum et al les deux exclusivement par des cations trivalents (Rittner & Glaum, 1994;Attfield et al, 1989), par une distribution statistique de cations di-et trivalents (Yahia et al, 2016;Souiwa et al, 2015b;Essehli et al, 2015), l'un par une ré partition statistique de cations di-et trivalents et l'autre uniquement par des cations di-ou trivalents (Souiwa et al, 2015a; Ben Smail & Zid, 2017b) ou l'un par des cations divalents et l'autre par des cations trivalents (Bouraima et al, 2016;Ouaatta et al, 2015;Alhakmi et al, 2013a,b;Assani et al, 2013;Korzenski et al, 1999;Hidouri et al, 2004;Kinomura et al, 1989). La derniè re ré partition cationique est observé e dans l'arsé niate objet de ce travail.…”
Section: Figureunclassified